The Factors Associated with the Incidence of Low Birth Weight LBW - Ngatimah Ngatimah; Dewi Ciselia; Satra Yunola; Suprida Suprida (Universitas Islam Jember, 2022)
Maternal and child health issues are still national priority in Indonesia. LBW cases are one of the major causes of infant mortality in Indonesia. Up to the policies to improve the health status of mothers and children have only focused on mothers and children, and rarely involved the participation of families. Low birth weight (LBW) the main cause of infant mortality before the age of one month (neonates). One of the causes LBW is anemia in pregnant women. The objective of this study is to reveal the relationship of anemia, preeclampsia and CED simultaneously with the incidence of LBW at Kayuagung Regional Public Hospital in Ogan Komering Ilir (OKI) Regency in 2021. This is an analytical survey study using cross sectional research. The population of this study was all mothers giving birth at Kayuagung Regional Public Hospital in 2021. 860 mothers in total, and the number of sample was 97 respondents. The sampling technique was systematic random sampling. The data analysis was chi square statistical test, p value ≤ α value (0,05). The result of this on 97 respondents revealed that there was a relationship between anemia and the incidence of LBW p value = 0,002, there was a relantionsjip betweenpreeclampsia and the incidence og LBW p value = 0,000, and there was a relantionship between CED and the incidence of LBW p value = 0,000. Based on the results of the study, it is expected that midwives improve health services to the community in order to reduce infant mortality.